Prooxidant activity of transferrin and lactoferrin (The Rockefeller University Press, 1990)
Acceleration of the autoxidation of Fe2+ by apotransferrin or apolactoferrin at acid pH is indicated by the disappearance of Fe2+, the uptake of oxygen, and the binding of iron to transferrin or lactoferrin. The product(s) formed oxidize iodide to an iodinating species and are bactericidal to Escherichia coli. Toxicity to E. coli by FeSO4 (10(-5) M) and human apotransferrin (100 micrograms/ml) or human apolactoferrin (25 micrograms/ml) was optimal at acid pH (4.5- 5.0) and with logarithmic phase organisms. Both the iodinating and bactericidal activities were inhibited by catalase and the hydroxyl radical (OH.) scavenger mannitol, whereas superoxide dismutase was ineffective. NaCl at 0.1 M inhibited bactericidal activity, but had little or no effect on iodination. Iodide increased the bactericidal activity of Fe2+ and apotransferrin or apolactoferrin. The formation of OH.was suggested by the formation of the OH.spin-trap adduct (5,5- dimethyl-1-pyroline N-oxide [DMPO]/OH)., with the spin trap DMPO and the formation of the methyl radical adduct on the further addition of dimethyl sulfoxide. (DMPO/OH).formation was inhibited by catalase, whereas superoxide dismutase had little or no effect. These findings suggest that Fe2+ and apotransferrin or apolactoferrin can generate OH.via an H2O2 intermediate with toxicity to microorganisms, and raise the possibility that such a mechanism may contribute to the microbicidal activity of phagocytes.